Alpha-class glutathione S-transferases involved in the detoxification of aflatoxin B1 in ducklings - Zhang, Yu; Cao, Ke-Xin; Niu, Qin-Jian; Deng, Jiang; Zhao, Ling; Khalil, Mahmoud Mohamed; Karrow, Niel Alexander; Kuča, Kamil; Sun, Lv-Hui (Food and chemical toxicology, 2023)
The objective of this study was to identify the key glutathione S-transferase (GST) isozymes involved in the detoxification of Aflatoxin B1 (AFB1) in ducks' primary hepatocytes. The full-length cDNA encoding the 10 GST isozymes (GST, GST3, GSTM3, MGST1, MGST2, MGST3, GSTK1, GSTT1, GSTO1 and GSTZ1) were isolated/synthesized from ducks' liver and cloned into the pcDNA3.1(+) vector. The results showed that pcDNA3.1(+)-GSTs plasmids were successfully transferred into the ducks' primary hepatocytes and the mRNA of the 10 GST isozymes were overexpressed by 1.9-3274.7 times. Compared to the control, 75 μg/L (IC30) or 150 μg/L (IC50) AFB1 treatment reduced the cell viability by 30.0-50.0% and increased the LDH activity by 19.8-58.2% in the ducks' primary hepatocytes. Notably, the AFB1-induced changes in cell viability and LDH activity were mitigated by overexpression of GST and GST3. Compared to the cells treated with AFB1, exo-AFB1-8,9-epoxide (AFBO)-GSH, as the major detoxified product of AFB1, was increased in the cells overexpression of GST and GST3. Moreover, the sequences, phylogenetic and domain analysis revealed that the GST and GST3 were orthologous to Meleagris gallopavo GSTA3 and GSTA4. In conclusion, this study found that the ducks' GST and GST3 were orthologous to Meleagris gallopavo GSTA3 and GSTA4, which were involved in the detoxification of AFB1 in ducks' primary hepatocytes.
Keywords: játra; Ducks; Phylogeny; Aflatoxin B1; Aflatoxin B(1); aflatoxin B1; zvířata; Glutathione; Glutathione S-transferase; Glutathione Transferase; Hepatotoxicity; kachny; Isoenzymes; Liver; izoenzymy; fylogeneze; Duck; glutathion; Animals; glutathiontransferasa; Detoxification